Diversity of Phenolic Profiles in Peel of an Iranian Pomegranate Cultivar (Punica granatum L.): Phenolic Profiles in Peel of Iranian Pomegranate - Taleghani, Akram; Akbari, Reza (Iranian Journal of Pharmaceutical Sciences, 2021)
Pomegranate (Punica granatum L.) is one of the oldest known fruits native to Iran. In addition to multiple studies carried out on different parts of pomegranate, the peels are noted due to various phytochemicals in different colors and regions. In the present study, major anthocyanins and non-anthocyanins of an Iranian black pomegranate cultivar (i.e., pomegranate samples of Ghaemshahr, Iran) were analyzed using high-performance liquid chromatography-mass spectrometry. In total, 30 compounds were obtained from pomegranate peels. Among these compounds, 5 anthocyanins, 1 gallotannin, 15 ellagitannins, 4 hydroxybenzoic acids, 2 gallagyl esters, 1 dihydroflavonol, and 7 hydroxycinnamic acids were identified based on their fragmentation patterns and ultraviolet spectra. Among the varieties of Iranian pomegranates, the anthocyanins of peonidin-hexoside and cyanidin-pentoside were identified in this species for the first time. Peonidin-hexoside, caffeic acid, coumaric acid-hexoside, and galloyl-hexoside were major phenolic compounds. In addition, the antioxidant activity of different fractions was tested using DPPH free radical scavenging in vitro assay (IC50: 133.13-557.23 μg/mL). The obtained results of this study highlighted that this cultivar can be an important candidate for future new drug discoveries.